Proceedings of the Fist International Conference on Advanced Scientific Innovation in Science, Engineering and Technology, ICA 2021
DOI: 10.4108/eai.16-5-2020.2304201
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Power Aware Algorithm for Optimizing Energy Consumption of Cloud Resources Using Multi Agent Model

Abstract: Cloud computing offers different kinds of resources to the user based on the current need. The resource includes hardware, software and platform through virtualization. User requirements are mapped to the corresponding Virtual Machine (VM) by the host of the data center. Every resource in the data center consumed a considerable amount of energy. The existing power aware models are used to minimize the energy consumption but it follows only one specific layer in the cloud. These methods suffer from performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…In Raiciu et al [9], Bodik et al [10], and Detal et al [11], authors worked on the dynamic management of cloud assets. Researchers also focused on fault tolerance [10], energy consumption [12][13][14][15][16], and data security [17][18][19]. It has been found that energy consumption is one of the most critical factors for cloud computing networking as it requires to be in service all the time.…”
Section: Introductionmentioning
confidence: 99%
“…In Raiciu et al [9], Bodik et al [10], and Detal et al [11], authors worked on the dynamic management of cloud assets. Researchers also focused on fault tolerance [10], energy consumption [12][13][14][15][16], and data security [17][18][19]. It has been found that energy consumption is one of the most critical factors for cloud computing networking as it requires to be in service all the time.…”
Section: Introductionmentioning
confidence: 99%